STUDI LITERATURE PENGETAHUAN IBU TENTANG PENCEGAHAN DAN PENANGANAN ANEMIA PADA MASA KEHAMILAN - sitti Rahmatia; Kurnia Rahma Syarif; Naharia LaUbo; Silma Eka Ananda (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2023)
Mother's knowledge is one of the factors that stimulate or stimulate the realization of a health behavior. it is expected that mothers have good behavior in order to reduce the risk of anemia during pregnancy. This study aims to determine the level of knowledge of mothers about the prevention and management of anemia during pregnancy. The research method uses a descriptive method by using literature studies in articles/journals that discuss maternal knowledge about the prevention and treatment of anemia during pregnancy. The results obtained from several journals that have been reviewed are the majority of pregnant women who have low knowledge about anemia due to maternal age, occupation, and education. The conclusion of the researcher is that knowledge of pregnant women is one of the important factors to reduce the risk of anemia during pregnancy. healthy behavior and can reduce the risk of death in pregnant women and fetuses